Recombinant factor VIII Fc fusion protein: extended‐interval dosing maintains low bleeding rates and correlates with von Willebrand factor levels. (10th October 2014) - Shapiro, A. D.; Ragni, M. V.; Kulkarni, R.; Oldenberg, J.; Srivastava, A.; Quon, D. V.; Pasi, K. J.; Hanabusa, H.; Pabinger, I.; Mahlangu, J.; Fogarty, P.; Lillicrap, D.; et al.
Summary Background Routine prophylaxis with replacement factor VIII (FVIII) – the standard of care for severe hemophilia A – often requires frequent intravenous infusions (three or four times weekly). An FVIII molecule with an extended half‐life could reduce infusion frequency. The A‐LONG study established the safety, efficacy and prolonged pharmacokinetics of recombinant FVIII Fc fusion protein (rFVIIIFc) in previously treated adolescents and adults with severe hemophilia A. Objective In this post hoc analysis, we investigated the relationship between subjects' prestudy (FVIII) and on‐study (rFVIIIFc) regimens. Methods We analyzed two subgroups of subjects: prior prophylaxis and on‐study individualized prophylaxis (n = 80), and prior episodic treatment and on‐study weekly prophylaxis (n = 16). Subjects' prestudy dosing regimens and bleeding rates were compared with their final rFVIIIFc regimens and annualized bleeding rates (ABRs) in the last 3 months on‐study. Dosing regimen simulations based on population pharmacokinetics models for rFVIII and rFVIIIFc were performed. Results As compared with their prestudy regimen, 79 of 80 (98.8%) subjects on individualized rFVIIIFc prophylaxis decreased their infusion frequency. Overall ABRs were low, with comparable factor consumption. Longer dosing intervals, including 5‐day dosing, were associated with higher baseline von Willebrand factor antigen levels. Simulated dosing regimens predicted a greater proportion of subjects with steady‐state FVIII activity trough levels of ≥ 1 IU dL−1 (1%) with rFVIIIFc than with equivalent rFVIII regimens. Conclusion These results suggest that patients on rFVIIIFc prophylaxis can reduce their infusion frequency as compared with their prior FVIII regimen while maintaining low bleeding rates, affording more patients trough levels of ≥ 1 IU dL−1 than with rFVIII products requiring more frequent dosing regimens.